Average Error: 0.0 → 0.0
Time: 13.9s
Precision: 64
$\frac{1}{\cosh x}$
$\sqrt[3]{\frac{1}{\cosh x} \cdot \left(\frac{1}{\cosh x} \cdot \frac{1}{\cosh x}\right)}$
\frac{1}{\cosh x}
\sqrt[3]{\frac{1}{\cosh x} \cdot \left(\frac{1}{\cosh x} \cdot \frac{1}{\cosh x}\right)}
double f(double x) {
double r16444656 = 1.0;
double r16444657 = x;
double r16444658 = cosh(r16444657);
double r16444659 = r16444656 / r16444658;
return r16444659;
}


double f(double x) {
double r16444660 = 1.0;
double r16444661 = x;
double r16444662 = cosh(r16444661);
double r16444663 = r16444660 / r16444662;
double r16444664 = r16444663 * r16444663;
double r16444665 = r16444663 * r16444664;
double r16444666 = cbrt(r16444665);
return r16444666;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$\frac{1}{\cosh x}$
2. Using strategy rm
$\leadsto \color{blue}{\sqrt[3]{\left(\frac{1}{\cosh x} \cdot \frac{1}{\cosh x}\right) \cdot \frac{1}{\cosh x}}}$
$\leadsto \sqrt[3]{\frac{1}{\cosh x} \cdot \left(\frac{1}{\cosh x} \cdot \frac{1}{\cosh x}\right)}$
herbie shell --seed 1